Depth resolved label-free multimodal optical imaging platform to study morpho-molecular composition of tissue. Issue 5 (18th March 2019) - Andreana, Marco; Sentosa, Ryan; Erkkilä, Mikael T.; Drexler, Wolfgang; Unterhuber, Angelika
Abstract : The presented multi-modal platform combines optical coherence tomography, two-photon excited fluorescence, second harmonic generation and anti-Stokes Raman scattering to provide molecular and structural information of tissue in a fast and non-invasive manner. Abstract : Multimodal imaging platforms offer a vast array of tissue information in a single image acquisition by combining complementary imaging techniques. By merging different systems, better tissue characterization can be achieved than is possible by the constituent imaging modalities alone. The combination of optical coherence tomography (OCT) with non-linear optical imaging (NLOI) techniques such as two-photon excited fluorescence (TPEF), second harmonic generation (SHG) and coherent anti-Stokes Raman scattering (CARS) provides access to detailed information of tissue structure and molecular composition in a fast, label-free and non-invasive manner. We introduce a multimodal label-free approach for morpho-molecular imaging and spectroscopy and validate the system in mouse skin demonstrating the potential of the system for colocalized acquisition of OCT and NLOI signals.